The Effectiveness Of Health Education On The Behavior Of Choosing Tracks On Students In Sd Negeri 03 Kota Baru Lahat - Sri Hartati; Eri Fauziah (STRADA : Jurnal Ilmiah Kesehatan, 2021)
School age children need sufficient food in quantity and quality in order to have a good nutritional status. The habit of children not having breakfast at home coupled with the habit of parents giving pocket money to children is a triggering factor for the emergence of unhealthy snacking behavior at school. Children often buy snacks. Carelessly and choose interesting types of food with low quality snacks and poor food ingredients. This study aims to determine the differences before and after being given health education on the behavior of choosing snacks for fifth grade students at SD Negeri 03 Kota Baru Lahat in 2019. This study is a quantitative study using a quasi experimental design with one group pre-test and post-test models. The sample in this study amounted to 46 people, taken through a total sampling method to all students in class V (Five) SD Negeri 03 Kota Baru